Transformacja w sztuce w postkomunistycznej Europie - Radomska, Magdalena (Artium Quaestiones, 2019)
The paper focuses on the ways of visualizing political and economic transformation in the works of artists from post-communist Europe mainly in the 1990s. Those works, which today, in a wide geographical context, may be interpreted as problematizing the idea of transformation, were often originally appropriated by such discourses of the post-transformation decade as the art of the new media and technology (Estonia), performance (Russia), feminism (Lithuania), body art (Hungary), and critical art (Poland), which marginalized the problem of transformation. Analyses of the works of artists from Lithuania, Estonia, Hungary, Bulgaria, and Russia make it possible to determine and problematize the poles of transformation in a number of ways, pointing at the inadequacy of those poles which traditionally spread from the end of totalitarian communism to democracy identified with free market economy. By the same token, they allow one to question their apparent antithetical character which connects the transformation process to the binary structures of meaning established in the period of the Cold War. The presented analyses demonstrate that the gist of the transformation was not so much the fall of communism, which is surviving in the post-1989 art of East-Central Europe due to the leftist inclinations of many artists with a Marxist intellectual background, but the collapse of the binary structure of the world. Methodologically inspired by Boris Buden, Susan Buck-Morss, Marina Gržinić, Edit András, Boris Groys, Alexander Kiossev, and Igor Zabel, they restore the revolutionary character of 1989 and, simultaneously, a dialectical approach to the accepted poles of the transformation. An example of ideological appropriation, which may be interpreted as problematizing the political transformation, is Trap. Expulsion from Paradiseby the Lithuanian artist Eglė Rakauskaitė. The first part of the paper focuses on Jaan Toomik’s May 15-June 1, 1992, interpreted in the theoretical terms proposed by Marina Gržinić and Boris Groys as a work of art that visualizes the concept of post-communism as excrement of the transformation process. Placed in the context of such works as In Fat(1998) by Eglė Rakauskaitė, 200 000 Ft(1997) by the Hungarian artist Kriszta Nagy or Corrections(1996-1998) by Rassim Krastev from Bulgaria, Toomik’s work is one of many created at that time in East-Central Europe, which thematized the transformation process with reference to the artist’s body. Krastev’s Correctionsproblematizes the transformation as a process of self-colonization by the idiom of the West, as well as a modification of the utopia of production, one aspect of which was propaganda referring to the body, changing it in an instrument that transformed the political order into a consumerist utopia where bodies exist as marketable products. The part titled, “The Poles of Transformation as a Function of the Cold War,” focuses on A Western View(1989) by the Bulgarian artist Nedko Solakov and This is my blood(2001) by Alexander Kossolapov from Russia. In a theoretical context drawn from the texts by Zabel, Buden, and Ekaterina Degot, Solakov’s work has been interpreted as problematizing the transformation understood as refashioning the world, no longer based on the bipolar division into East and West. The paper ends with an analysis of Cunyi Yashi, a work of the Hungarian artist Róbert Szabó Benke, which problematizes the collapse of the bipolar world structure in politics and the binary coding of sexual identity. In Szabó Benke’s work, the transformation is represented as rejection of the binary models of identity – as questioning their role in the emergence of meanings in culture.